Proceedings 2019 Workshop on Usable Security 2019
DOI: 10.14722/usec.2019.23016
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Mobile Application to Support Social Processes for Privacy Decisions

Abstract: People often rely on their friends, family, and other loved ones to help them make decisions about digital privacy and security. However, these social processes are rarely supported by technology. To address this gap, we developed an Android-based mobile application ("app") prototype which helps individuals collaborate with people they know to make informed decisions about their app privacy permissions. To evaluate our design, we conducted an interview study with 10 college students while they interacted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…In a follow-up study, Kropcynski et al [30] further validated the applicability of the model of community oversight within older adult communities. Therefore, we adapted and implemented their initial app design [4], which was instantiated from the model of community oversight to assess whether this approach would be suitable for the unique relationship between parents and teens.…”
Section: Design Of the Co-ops Appmentioning
confidence: 99%
See 2 more Smart Citations
“…In a follow-up study, Kropcynski et al [30] further validated the applicability of the model of community oversight within older adult communities. Therefore, we adapted and implemented their initial app design [4], which was instantiated from the model of community oversight to assess whether this approach would be suitable for the unique relationship between parents and teens.…”
Section: Design Of the Co-ops Appmentioning
confidence: 99%
“…For example, teens did not expect their parents needed help with their online safety, and were thus reluctant to provide such oversight. This reluctance of users to participate in oversight to others was a concern raised by Aljallad et al [4] in their initial study of the CO-oPS idea. Another threat to participating in collaborative privacy management is having doubts about the feedback given by others.…”
Section: Implications For Collaborative Privacy Management Beyond Fam...mentioning
confidence: 99%
See 1 more Smart Citation
“…Users are also influenced by others' privacy and security practices to make changes to their own privacy behaviors [11-13, 16, 25]. Therefore, networked privacy researchers have called for more collaborative approaches within an individual's networks so that people can exchange mobile privacy, safety, and security support with one another [3,9,12]. However, Kropczynski et al [18] have reported that in order to get effective support for digital privacy and security management, one must have some technical expertise in their community.…”
Section: Collaborative Approaches For Mobile Privacy Safety and Securitymentioning
confidence: 99%
“…Unfortunately, the majority of U.S. adults lack knowledge regarding how to protect their digital privacy and security, which increases the potential for privacy and security violations [27]. Due to the lack of mobile privacy knowledge at an individual level, networked privacy researchers (e.g., [3,9,12]) have suggested adopting more collaborative and community-based approaches for managing digital privacy and security, where trusted community members (e.g., family, friends, co-workers) can work together to help keep one another safe online. Interestingly, some research has even shown how adult family members often rely on younger generations of their family (e.g., their teens) for technology support, as youth may be tech-savvier than their parents [10,26].…”
Section: Introductionmentioning
confidence: 99%